Dynamics of the density of lawn grass and herbage on loamy and sandy soils - A A Poddubsky (RUDN Journal of Agronomy and Animal Industries, 2017)
Conducted research on the dynamics of the density of single-species and mixed grass crops on sod-podzolic soils of the Ryazan region. The estimation of the density of turf grass stands in the years 2012-2014 studies found that the highest density had a single-species crops: Kentucky bluegrass, red fescue, bent grass selenobrachys, and among mixed crops - a three-component grass mixture (red fescue, Kentucky bluegrass, bent grass selenobrachys) and four-component mixture (selenobrachys bent grass, red fescue, Kentucky bluegrass, red fescue). The lowest density of planting was installed at the perennial ryegrass in the second and third years and three-component grass mixture (red fescue, sheep's fescue, perennial ryegrass) in the third year of life of grass. The trend of higher density turf grass stands revealed in experiment 1 for loamy soils compared to sandy loam.